2009
DOI: 10.1007/s00445-009-0274-x
|View full text |Cite
|
Sign up to set email alerts
|

Merging eruption datasets: building an integrated Holocene eruptive record for Mt Taranaki, New Zealand

Abstract: Acquiring detailed eruption frequency datasets for a volcano system is essential for realistic eruption forecasts. However, accurate datasets are inherently difficult to compile, even if one or more well-dated eruption records are available. A single record typically underrepresents the eruption frequency, while combining two or more records may result in an overrepresentation. Although glass compositions have proven to be successful in tephrochronological studies of dominantly rhyolitic tephras; microlitic gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 45 publications
0
50
0
Order By: Relevance
“…There is also 682 a strong effect of mixing on concentration of refractory trace elements in hybrid magmas. Geochemical studies of the detailed tephra record for individual volcanoes are few (e.g., 712 Donoghue et al 2007;Oladottir et al 2008;Turner et al 2009) though they permit to study 713 evolution of volcanoes with great details and sometimes show certain regular temporal patterns 714 in the eruptive records (Oladottir et al 2008). Our work at Shiveluch and Kliuchevskoi 715 volcanoes also shows that both volcanoes exhibit wave-like changes of SiO 2 contents in glass 716 from rapidly quenched tephras during Holocene roughly correlating in time between the 717 volcanoes (Portnyagin et al 2009(Portnyagin et al , 2011.…”
Section: Bulk Compositions Of Shiveluch Tephra 348mentioning
confidence: 99%
“…There is also 682 a strong effect of mixing on concentration of refractory trace elements in hybrid magmas. Geochemical studies of the detailed tephra record for individual volcanoes are few (e.g., 712 Donoghue et al 2007;Oladottir et al 2008;Turner et al 2009) though they permit to study 713 evolution of volcanoes with great details and sometimes show certain regular temporal patterns 714 in the eruptive records (Oladottir et al 2008). Our work at Shiveluch and Kliuchevskoi 715 volcanoes also shows that both volcanoes exhibit wave-like changes of SiO 2 contents in glass 716 from rapidly quenched tephras during Holocene roughly correlating in time between the 717 volcanoes (Portnyagin et al 2009(Portnyagin et al , 2011.…”
Section: Bulk Compositions Of Shiveluch Tephra 348mentioning
confidence: 99%
“…15). These biotite differences provided the key to identifying one of the distal tephras in the Kaipo bog sequence in eastern North Island that previously had been misidentified because its major-element glass chemistry matched that of two eruptives identical in age but derived from different volcanic sources (Shane et al, 2003a(Shane et al, , 2003b Analyses of Fe-Ti oxides, titanomagnetite and ilmenite, by EPMA have been useful for tephra fingerprinting for many years (e.g., Westgate and Evans, 1978;Hogg and McCraw, 1983;Beaudoin and King, 1986;Julian et al, 1988;Cronin et al, 1996;Smith et al, 2002;McHenry, 2005;Turner et al, 2009). The validity of such analysis as a correlation tool was supported by crystal field theory (Hodder, 1981).…”
Section: In Favourable Circumstances Individual Tephras May Be Identmentioning
confidence: 99%
“…She demonstrated that a single core or site is not sufficient to develop a regional stratigraphic record because of erosion and reworking, and that composite overlapping records, rather than a principal reference section or core, may be required to develop a comprehensive record (see also Turner et al, 2009;Schiff et al, 2010). A similar finding was reported for northern New Zealand at Lake Maratoto where Green and Lowe (1985) and Lowe (1988b) used 33 lake cores in total, and multiple peat cores, to reconstruct the lake"s tephrostratigraphic record and its developmental history since ca.…”
Section: Reworking Of Tephras and Taphonomic Considerationsmentioning
confidence: 99%
See 2 more Smart Citations